2017
DOI: 10.1111/1365-2435.12952
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic matter availability and climate drive latitudinal patterns in bacterial diversity from tropical to cold temperate forests

Abstract: Abstract1. Bacteria are one of the most abundant and diverse groups of micro-organisms and mediate many critical terrestrial ecosystem processes. Despite the crucial ecological role of bacteria, our understanding of their large-scale biogeography patterns across forests, and the processes that determine these patterns lags significantly behind that of macroorganisms.2. Here, we evaluated the geographic distributions of bacterial diversity and their driving factors across nine latitudinal forests along a 3,700-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 61 publications
5
80
2
Order By: Relevance
“…leaved species, produces large amounts of litter with a high organic matter content. In natural forest ecosystems, the decomposition of litter into soil organic matter may be the main reason for the increase in soil organic matter [47]. In our study, the five forest types had a stand age of about 50 years, with a similar length of time to accumulate organic matter.…”
Section: Variation In Soil Organic Matter Under Different Forest Typesmentioning
confidence: 73%
See 1 more Smart Citation
“…leaved species, produces large amounts of litter with a high organic matter content. In natural forest ecosystems, the decomposition of litter into soil organic matter may be the main reason for the increase in soil organic matter [47]. In our study, the five forest types had a stand age of about 50 years, with a similar length of time to accumulate organic matter.…”
Section: Variation In Soil Organic Matter Under Different Forest Typesmentioning
confidence: 73%
“…The value of the comprehensive evaluation directly reflects the water conservation capacity of different forest types [47]. The larger the comprehensive evaluation value, the higher the effect of the corresponding water conservation capacity [48].…”
Section: Soil and Water Conservation Functionmentioning
confidence: 99%
“…Regardless of the causal mechanisms, our results were robust and some trait changes were consistent among the many habitat and soil types. Given the considerable changes in C:N:P and other soil traits, an in-situ C. micronesica tree creates the conditions to increase α-diversity of soil microbiota [33]. The influence of C. micronesica trees on the heterogeneity of soil nitrogen is of particular interest, as nitrogen availability directly affects growth of primary producers in a landscape then exerts cascading effects on food web functioning among many trophic levels [34].…”
Section: Synthesismentioning
confidence: 99%
“…Using high‐throughput 16S rRNA gene sequencing, Tian et al. () investigated the geographical distribution of bacterial diversity and found that soil bacterial richness and phylogenetic diversity increased linearly with latitude. Soil pH and substrate availability were the most important edaphic drivers for bacterial community structure along the transect.…”
Section: Overview Of the Functional Traits That Were Studied Along Thmentioning
confidence: 99%